Laparoscopic diagnosis in traumatic and non-traumatic acute abdomen - Genta, Fernando; Caraballo, Mónica; Cassinelli, Jorge; Terra, Daniel; Voelker, Ricardo (Cirugía del Uruguay, 2002)
The prospective study was conducted in arder to eva/uate the use of !aparoscopy in the diagnosis of traumatic and non-traumatic acute abdominal urgencies. Patients in whom diangosis presented doubts were studied through fibrolaparoscopy. Procedures performed between January 1994 and April 1998 amounted to 280, of which 170 corresponded to acute non-traumatic abdominal cases and the remaining 11 O to acute trauma tic abdominal injury.